Sourcing and usage of standard cassava cuttings by farmers in Egbeda local government area of Oyo state (2013)
The recent trend of demand for cassava provoked by policy support for its production suggests that cassava farmers can increase cassava production if there are available clean planting materials. Getting standard cassava cuttings by farmers will help them increase their production to meet global cassava competitiveness. However; data on sourcing and use of standard cassava cuttings among farmers is scanty. Sourcing and use of standard cassava cuttings in Egbeda Local Government area of Oyo State was investigated in this study. A multi-stage sampling technique was used to select respondents for this study. Seventy percent of rural wards totalling 5 wards and one third of villages in these wards (30) were randomly selected. Fifty percent of total number of cassava farmers (241) were systematically selected resulting in a total of 120 cassava farmers. The data for this study were obtained through the use of interview schedule. Data were analysed using frequency counts, percentages and chi-square at p=0.05. Results indicate that mean age, family and farm size were 52.4 years, 7 persons and 3.6 acres respectively. Most respondents were male (85.0%), married (95.8%) and had one form of education or the other (60.7%). Farmers obtained standard cassava cuttings mainly from neighbours/friends (84.2%) and open market (49.2%). While 46.7% had high knowledge of features of standard cassava cuttings, 64.3% of farmers planted the standard cuttings twice a year. Benefits that had accrued to farmers utilising standard cassava cuttings included high yield (99.2%), early maturity (98.3%) and high income (98.3%). They were however constrained by scarce standard cuttings (95.8%), delayed process of getting the cuttings (95.0%) and long distance between farmers' cassava farms and sources of standard cassava cuttings (79.2%). Farmers' sex (x2 =2,154), age (x2 =1.312), marital status (x2 =0.088), and educational level (x2= 3.642) had no significant relationship with their use of standard cassava cuttings. It is recommended that both government and research institutes should readily make available standard cassava cuttings given its inherent benefits and farmers' readiness to use the improved cuttings.